Tudo que desmancha no ar é sólido: a luta de classes no regime de informação fundiário brasileiro - Figueira, Monique (2023)
The so-called information society still sees Brazil as a sum of hereditary captaincies. Here, scorched-earth political economy has been undermining our public good for over five centuries. Information on national land tenure is not reliable, but closed and disperse between different public and private systems. Rather than a technical problem, it is about ideology, because in capitalism private property is sacred, but we need a secular State. At the macro level, material disengagement becomes universal, while the fallacy of the technological cloud serves as epitome for alienation, as nothing hovers abstractly without material ties to reality. Harvey’s overview (2022) on the spheres of totality, based on Marx's legacy, served to entitle the six chapters/papers presented in the thesis: production of life, social relations, mental conceptions, technology, nature and structure of the State. Chaos in Brazilian land tenure data has long been reported, but not in information sciences. From qualitative documentary research, the thesis is based on the political economy of information in order to characterize the Brazilian land information regime, encompassing not only the cadastral flows, but the expanded circuit of the document. In the context of class struggle, institutionality marginalizes counter-hegemonic forms of producing the space, such as the manifestations of native peoples, represented by the Yanomami, and social movements, like the landless workers. The bridge with the dialectic theory of information and the open systems perspective roots us back in the plurality of space and communication. Seeking the relationship between knowledge and territory, inherent to life, the research departs from information as matter and returns to it as common good.